Long-term time-series study of salp population dynamics in the Sargasso Sea - Stone, Joshua P.; Steinberg, Deborah K. (Marine Ecology Progress Series, 2014)
Salps are bloom-forming, pelagic tunicates with high grazing rates on phytoplankton, with the potential to greatly increase vertical particle flux through rapidly sinking fecal pellets. However, the frequency and causes of salp blooms are not well known. We quantified salps from day and night zooplankton net tows in the epipelagic zone of the North Atlantic subtropical gyre as part of the Bermuda Atlantic Time-series Study (BATS). Salp species and size were quantified in biweekly to monthly tows from April 1994 to November 2011. Twenty-one species of salps occurred at the BATS site over this time period, and the most common bloom-forming salps were Thalia democratica, Salpa fusiformis, Weelia (Salpa) cylindrica, Cyclosalpa polae, and Iasis zonaria. Five species of salps exhibited diel vertical migration, and salp abundances varied seasonally, with T. democratica, S. fusiformis, and C. polae blooms coincident with the spring phytoplankton bloom, and W. cylindrica blooms occurring more often in late summer. For T. democratica, mean annual biomass increased slightly over the time series and was elevated every 3 yr, and biomass increased in the presence of cyclonic mesoscale eddies. Decadal climate oscillations and biogeochemical conditions influenced multi-year trends in salp abundance and biomass. Both total salp and T. democratica abundance were positively correlated with primary production, total salp biomass was positively correlated with the North Pacific Gyre Oscillation, and T. democratica biomass was negatively correlated with the Pacific Decadal Oscillation. These salp bloom dynamics have important implications for planktonic food web interactions and biogeochemical cycling.